Experimental investigation on effect of zinc oxide nanofluid on performance, emission and combustion characteristics of CI engine fuelled with waste cooking oil biodiesel. (December 2020) - Ramanathan, V; Jaikumar, M; Aleem, Shaik Abdul; Induja, S; SangeethKumar, E
Abstract: Environmental effluence and fossil fuels exhaustion are the main reasons to use alternate biofuels worldwide in engines. Many researchers focused their research on biodiesel which were extracted from eatable and non-eatable vegetable oils, used them in diesel engines. In this context, biodiesel derived from Waste Cooking Oil (WCO) was taken as a substitute fuel for diesel engine because of two reasons; one reason was some of the properties of this biodiesel were very nearer to diesel and another reason was giving second life to the waste cooking oil instead of disposing of in the land. In the first stage, Waste cooking oil Biodiesel (WCOB) was produced from WCO by transesterification process and experiment was carried out using diesel and WCOB and considered as base readings. In the second stage, Zinc oxide nanofluid in the mass proportions of 50ppm, 75ppm and 100 ppm were synthesised using a novel wet chemical method and blended with WCOB and considered fuels as WCOBZN50, WCOBZN75 and WCOBZN100 and their properties were tested. Then the experiment was conducted in a fully equipped engine test set up. The engine was loaded at various loading conditions. The readings were measured and analysed. The results exhibited that the blending of zinc oxide nanofluids with WCOB improved engine performance characteristics. Also, it was observed that the addition of zinc oxide nanofluids reduced the engine tailpipe emissions compared to neat WCOB. It was also found that the combustion characteristics of ZnO nano blended biodiesel were increased marginally.